PEMANFAATAN ABU SEKAM PADI SEBAGAI BAHAN CAMPURAN BETON AGROPOLYMER - Musbar Musbar; Faisal Rizal; Herri Mahyar (Politeknik Negeri Lhokseumawe, 2010)
Constribution of production PC every year at glasshouse emission continue to experience of increase, estimated about 7% from totalizing the glasshouse emission transmitted to atsmosphere earth. On that account, is very needed the new inventions of concrete technology to produce the friendly environment. Some alternatives among its by making the concrete polymer which materials base natural, be like fly ash and rice husk ash ( RHA ) . this research use the RHA upon which mixture to make the concrete agropolymer. Concrete agropolymer use fixative of silicate sodium condensation mixture, hydroxide sodium and RHA. Variable remain to this research is strength the concrete agropolymer. Free variable consist of the ratio variation water and agropolymer solid that is 0,6 and 0,7, treatment time during 3,7, 14 and 21 day. Temperature treatment of object test at room temperature, each;every variation made by the object test the cube with side of 10 cm counted 5. This research can give the alternative to invention of friendly concrete of environment by exploiting the waste materials natural agricultural produce, but not yet application can at building construction because of strength depress the concrete still lower. Strength depress the obtained by concrete range from 4 - 5 Mpa at the age of concrete of 21 day. It’s needed to do the further research to get the ideal composition of materials concrete agropolimer this so that can be obtained the strength depress the application concrete able to building construction.Keyword : RHA, agropolymer, concrete strength